(untitled) (Archive of Conferences, 2021)
Genetically modified (GM) products are completely identical to their natural samples in their main characteristics, such as color, smell, and appearance [2,3,5,8,9,10,11].Genetic modification studies are also conducted on animals. In the case of animals, research is mainly aimed at improving disease resistance, controlling their growth, or changing the quality of wool and milk components. As a result of these studies, fish became the only animal produced economically [1,4,6,7,12].The purpose of this study was to develop a method for evaluating the effect of a genetically modified product on the morphological parameters of the liver of laboratory animals in an experiment